A Cadaveric Study of Dye Spreading: Determining the Ideal Injection Pattern for Masseter Hypertrophy. Issue 10 (October 2021) - Sermswan, Peerada; Tansatit, Tanvaa; Meevassana, Jiraroch; Panchaprateep, Ratchathorn
Abstract : BACKGROUND: Masseter hypertrophy is the main cause of an asymmetrical and squared lower facial contour in the Asian community. Botulinum toxin injection technique is crucial to treat this condition. OBJECTIVE: To improve injection techniques for masseter hypertrophy by elucidating the distribution of the injections within the masseter. METHODS: Thirty masseter muscles were divided into 6 groups of 5 muscles each. Each group received one 0.2- or 0.3-mL injection at Point A, B, or C according to a three-point technique. Muscle dimensions and dye of the primary and secondary dye spreading were measured. RESULTS: The average muscle length, width, and thickness were 69.87, 33.50, and 11.23 mm, respectively. The average primary longitudinal and horizontal spreading was 36.56 and 15.60 mm, respectively. No statistically significant difference was found between 0.2- and 0.3-mL injections at each point. CONCLUSION: The three-point technique best fits in the safe zone and should be the standard injection technique for masseter hypertrophy. Injection at Points B and C may create secondary spreading that affect the risorius muscle and the parotid gland which are the cause of asymmetrical smiling and xerostomia, respectively. The dosage should be adjusted according to the muscle volume and not only the thickness.